NILAI-NILAI RELIGIUS ISLAM DALAM ANTOLOGI CERPEN “CARAKU MENCINTAI KANG ALFI (ALFIYAH LATIN)” KARYA LIA HIMMATUL ULYA - Asngadi Rofiq; Moh. Syamsul Ma’arif (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
Literary works, especially short stories, are one of the teaching tools to develop the soul, humanize humans, and increase literary appreciation in depth and love, coloring short stories as a form of manifestation of life. As a form of literary work, the short story also tells about various human lives and their interactions with the environment and each other. One of the literary works in the form of short stories that really builds the soul and character of Indonesian children, one of which is a short story entitled